HUBUNGAN ANTARA GOOD CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN DENGAN KINERJA KEUANGAN - Malikah, Anik (IQTISHODUNA, 2009)
Agency Theory say if principal and agent (manager) have different of interest, will make agency conflict Separate of function about owner (shareholder) with manager will make negative effect like management freedom to maximize profit for themselves. This condition will happened caused asymmetry information among management and the other party that have no access information about firm. So there were not enough to oversee behavior of management.This Study intend to know the correlation Good Corporate Governance and ownership structure with company performance. Good corporate governance and ownership structure as independent variable and company performance as dependent variable. We use two pillar of Good Corporate Governance. There are transparency and accountability. Transparency is peroxide by disclosure of financial statement and accountabilities peroxide by accruals. Company performance is peroxide by Tobin's Q.The population are company that list in LQ 45 during 2 semester. The result of this study is: (1) there is no correlation about ownership structure with company performance. (2) There are no correlation about accountability with company performance, (3) there are significant correlation about transparency with company performance.